Cooling of liquid in a tube under rotation - Chou, Samuel Zi Han (2016)
An ideal polymerase chain reaction (PCR) process requires uniform temperature distribution during cooling. At the same time, a rapid rate of cooling is also preferred. In order to achieve the above requirements, the PCR machine is designed such that a cone containing the fluid is rotated about a disk. This study will analyze the temperature and velocity flow field patterns when the cone is rotating about the z, y and x-axis of the origin. It will also study the effect on temperature and velocity when the adiabatic base surface is removed. Computational fluid dynamics (CFD) is used to study the pattern of the flow in details. With CFD, the flow can be analyzed at different times during the cooling process. Some interesting features of the flow can be seen, one of which is the coriolis effect when the cone is rotating. Ansys CFX was the program used in the simulation. The flow can be described in two phases, the initial transient phase followed by the phase in which the velocity starts to decrease steadily from the apex. Features of the flow in these two phases are analyzed. From the findings, the rotation of the cone about z and y-axis gave better temperature homogenization than the rotation of the cone about the x-axis. Also, the removal of the adiabatic base surface gave better temperature homogenization and faster rate of cooling of the fluid.